2017
DOI: 10.3390/nu9060566
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of DHA Supplementation during Pregnancy: Child Adiposity Outcomes

Abstract: Investigating safe and effective interventions in pregnancy that lower offspring adiposity is important given the burden of obesity and subsequent metabolic derangements. Our objective was to determine if docosahexaenoic acid (DHA) given during pregnancy to obese mothers results in lower offspring adiposity. This study was a long-term follow-up of a randomized trial of mothers with gestational diabetes or obesity who were randomized to receive DHA supplementation at 800 mg/day or placebo (corn/soy oil) startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…A study led by Foster and colleagues studied the effects of DHA 800 mg/day supplementation vs. placebo in obese or diabetic pregnant women from 25–29 weeks of gestation. Differences of adiposity were not significant at birth, but at two and four years of follow-up, it was found that the BMI z-score was inversely associated with DHA intra-erythrocyte levels during the 36 th week of gestation [60]. Consistent with this finding, other trials found an association between DHA levels in human milk and BMI in childhood up to age seven.…”
Section: Impact Of Lcpufa On Mets Features During Lifetimementioning
confidence: 74%
“…A study led by Foster and colleagues studied the effects of DHA 800 mg/day supplementation vs. placebo in obese or diabetic pregnant women from 25–29 weeks of gestation. Differences of adiposity were not significant at birth, but at two and four years of follow-up, it was found that the BMI z-score was inversely associated with DHA intra-erythrocyte levels during the 36 th week of gestation [60]. Consistent with this finding, other trials found an association between DHA levels in human milk and BMI in childhood up to age seven.…”
Section: Impact Of Lcpufa On Mets Features During Lifetimementioning
confidence: 74%
“…It is important to note that most of the trials were primarily designed to investigate other outcomes in children such as neurological development, maternal insulin sensitivity; and growth measures in the offspring are also reported as secondary end-points [31, 34, 35, 39, 41, 44, 52, 54, 55]. Only two trials [47, 56] were originally designed to evaluate the effectiveness of prenatal n-3 LCPUFA supplementation on infant’s body composition.…”
Section: Resultsmentioning
confidence: 99%
“…One trial was conducted in atopic women [34] and another in women who were obese or had a history of gestational diabetes [55]. The remainder of the trials involved healthy pregnant women with non-complicated pregnancies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N-3 LCPUFAs are known to exhibit anti-inflammatory and anti-obesogenic properties in animals ( 70 ), although data in humans do not consistently confirm these associations. One study that provided DHA supplements to pregnant women with obesity or gestational diabetes found no significant effects on offspring adiposity outcomes ( 71 ). More data are needed to determine whether supplementation in pregnant women in higher BMI categories may be a promising intervention to reduce offspring obesity risk.…”
Section: Direction For Future Research: Targeting Lcpufa Interventionmentioning
confidence: 99%